2021
DOI: 10.21203/rs.3.rs-778412/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diagnostic Biomarker KIF23 is Associated With Immune Infiltration in Gastric Cancer

Abstract: Background: Kinesin family member 23 (KIF23), an index of tumor proliferation, can serve as a prognostic marker in numerous tumors. However, the relationship between KIF23 expression and immune infiltration and the diagnostic value of KIF23 remain unclear in GC (gastric cancer). This study aimed to explored the diagnostic value of KIF23 and its interactions with tumor-infiltrating immune cells in GC by bioinformatics analysis. Mothods: The relationship between clinicopathologic features and KIF23 expression wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Moreover, overexpressed MAT2A elevated the expression of RIP1 by increasing the H3K4 methylation at its promoter regions to induce the polarisation of M2 TAMs 47 . Several studies have demonstrated that the high expression of TUBA1A, ELK3, GKN2, COL1A2, RAI14, KIF23, GHRL, KCND2, SERPINE1, COL5A2, ALDOC and SLC38A2 and low expression of CD155 and AKR1B10 in GC indicate higher M2 TAM infiltration in the TME using data from public databases 93–107 . Furthermore, TAMs elevated the expression of PI3K‐γ by increasing the uptake of extracellular lipids, thereby inducing M2 phenotype polarisation 44 .…”
Section: The Role and Mechanism Of Tams In Gcmentioning
confidence: 99%
“…Moreover, overexpressed MAT2A elevated the expression of RIP1 by increasing the H3K4 methylation at its promoter regions to induce the polarisation of M2 TAMs 47 . Several studies have demonstrated that the high expression of TUBA1A, ELK3, GKN2, COL1A2, RAI14, KIF23, GHRL, KCND2, SERPINE1, COL5A2, ALDOC and SLC38A2 and low expression of CD155 and AKR1B10 in GC indicate higher M2 TAM infiltration in the TME using data from public databases 93–107 . Furthermore, TAMs elevated the expression of PI3K‐γ by increasing the uptake of extracellular lipids, thereby inducing M2 phenotype polarisation 44 .…”
Section: The Role and Mechanism Of Tams In Gcmentioning
confidence: 99%